Tribalism and Cultural Discontent in the Middle East - Esmailzadeh, Yaser (Journal of interdisciplinary studies, 2024)
The Middle East has long been characterized by political instability, violent conflicts, and cultural tensions. In recent years, the re-emergence of tribalism has further contributed to the deterioration of peace in the region. This essay investigates the influence of tribalism on cultural discontent and violence in the Middle East, arguing that it reinforces identity politics, exacerbates sectarianism, and undermines democratic values. These factors, in turn, fuel conflicts and hinder peace-building endeavors. The essay explores specific instances where tribalism has escalated violence, emphasizing the challenges of addressing its root causes. For a comprehensive understanding, there is a need to examine historical and contemporary factors that contribute to tribalism's growth and persistence. The complex interplay between tribalism and other socio-political dynamics highlights how these interactions exacerbate regional instability. The essay concludes by advocating for increased attention to cultural aspects of conflict and the necessity for more effective strategies to foster intercultural dialogue and understanding in the region.